2019
DOI: 10.1136/bcr-2018-228856
|View full text |Cite
|
Sign up to set email alerts
|

Infected aneurysm after returning from Southeast Asia: thinkBurkholderia pseudomallei!

Abstract: Melioidosis is a protean disease which is endemic to Southeast Asia and northern Australia. Here, we report a case of infected aortic aneurysm due to Burkholderia pseudomallei in an immunocompetent man 6 months after a trip to northern Malaysia. This patient initially received inappropriate surgical and antibiotic treatment, leading to a peri-prosthetic aortic infection with lumbar spondylitis and contiguous psoas muscle abscess. This case highlights the difficulty of diagnosing melioidosis given its diverse c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…It is documented that most patients with infected mycotic aneurysm secondary to melioidosis are male and aged 60 years [1,2,12,19]. Similarly, in our case series, the ages of eight subjects ranged from 48 to 69, with a median age of 61.5 years, all were indigenous males, and two [24], Case 12-14 [25], Case 15 [26], Case 16 [3], Case 17 [27], Case 18 [28], Case 19 [29], Case 20 [30], Case 21 [31], Case 22 [19], Case 23-24 [6], and Case 25-26 [10], Case 27 [52], Case 28 [18], Case 29 [32], Case 30 [33], Case 31 [41], Case 32 [35], Case 33 [36], Case 34 [8] Case 35 [37], Case36 [38], Case37 [39], and Case38 [40].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It is documented that most patients with infected mycotic aneurysm secondary to melioidosis are male and aged 60 years [1,2,12,19]. Similarly, in our case series, the ages of eight subjects ranged from 48 to 69, with a median age of 61.5 years, all were indigenous males, and two [24], Case 12-14 [25], Case 15 [26], Case 16 [3], Case 17 [27], Case 18 [28], Case 19 [29], Case 20 [30], Case 21 [31], Case 22 [19], Case 23-24 [6], and Case 25-26 [10], Case 27 [52], Case 28 [18], Case 29 [32], Case 30 [33], Case 31 [41], Case 32 [35], Case 33 [36], Case 34 [8] Case 35 [37], Case36 [38], Case37 [39], and Case38 [40].…”
Section: Discussionsupporting
confidence: 62%
“…The low proportion of cases in Australia compared with Malaysia might be also explained by a higher proportion of low-income households and less access to medical resources in Southeast Asian countries [11,13,45]. Interestingly, in accordance to the literature review revealed in Fig 3, the preponderance of cases was amongst the developed country travelers from developing countries, which also suggests that mycotic aneurysm secondary to melioidosis is actually being missed in endemic areas and diagnosed only when patients are managed in countries that are better resourced and where imaging is more widely available [2,9,23,24,27,38].The literature review demonstrated that Hainan was the main epidemic focus of melioidosis in China. In 2011 the Institute for Communicable Disease Control and Prevention of China established a working group to monitor the epidemiology of melioidosis throughout China, revealing the overwhelming majority of culture-confirmed cases were from Hainan (99.0%, 392/396, 3 from Guangxi and 1 from Guangdong) between 2002 and 2016, and septicaemia was the most common clinical manifestation (153/277, 55.2%) [15].Taken together, the mycotic aneurysm cases collected in Hainan Province in the present study can represent the general epidemiological features in China.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation